FRAGMENT DNA 387BP GENE LECTIN OF SOYBEAN (Glycne Max L.) MERIIL - Puspitaningrum, Rini; Amelia, Ria; Adisyahputra, Adisyahputra (LPPM Universitas Negeri Jakarta, 2017)
Lectin gene is a housekeeping gene that can be used as a molecular marker soybean (Glycine max (L.) Meriil.). This study aimed to obtain the identity of the lectin gene molecular markers for breeding purposes. This descriptive study was performed using PCR amplification and identification of sequences using a lectin gene fragment sequencing techniques and phylogenetic search using Mega Tree programme. The results obtained are lectin gene fragment along 387bp used primer Leic Foward GCGGAAACTGTTTCTTTCAGCTGG and primer Leic Reverse CCGGAAAGTGTCAAACTCAACAGCG.